2008
DOI: 10.1016/j.jpubeco.2007.11.005
|View full text |Cite
|
Sign up to set email alerts
|

School finance reform: Assessing general equilibrium effects

Abstract: In 1994 the state of Michigan implemented one of the most comprehensive school finance reforms undertaken to date in any of the states. Understanding the effects of the reform is thus of value in informing other potential reform initiatives. In addition, the reform and associated changes in the economic environment provide an opportunity to assess whether a simple general equilibrium model can be of value in framing the study of such reform initiatives. In this paper, we present and use such a model to derive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…(2) Do SFRs lead to enduring spending changes? Researchers have found that SFRs may affect marginal income tax rates (McGuire and Anderson, 2011), residential sorting (Tiebout, 1956), and shifting of income sources for school spending (Brunner and Sonstelie, 2003); be capitalized into housing prices (Epple and Ferreyra, 2008); and lead to loopholes or subsequent reforms to undo the effects of SFRs (Imazeki and Reschovsky, 2004). Accordingly, the effects of SFRs on school spending in the short run might be quite different from those in the long run.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Do SFRs lead to enduring spending changes? Researchers have found that SFRs may affect marginal income tax rates (McGuire and Anderson, 2011), residential sorting (Tiebout, 1956), and shifting of income sources for school spending (Brunner and Sonstelie, 2003); be capitalized into housing prices (Epple and Ferreyra, 2008); and lead to loopholes or subsequent reforms to undo the effects of SFRs (Imazeki and Reschovsky, 2004). Accordingly, the effects of SFRs on school spending in the short run might be quite different from those in the long run.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the evidence presented in this paper, these empirical findings are consistent with the predictions of the current model in the sense that a Foundation system may socially be beneficial over a Power-Equalizing system after accounting for the effects coming from the housing market and property tax revenues. While these results are consistent with this paper, Epple and Ferreyra (2008) do not model the political economy behind the Michigan reform but rather describe its effects. This paper analyzes welfare gains and provides conditions under which a system would be more likely to be chosen by majority voting.…”
Section: Many Researchers Have Examined State Level Public Education supporting
confidence: 75%
“…As described above, the latter is crucial to rationalize recent switches from Power-Equalizing to Foundation systems. In a similar spirit, Epple and Ferreyra (2008) examine general equilibrium effects of school funding reform of 1994 in Michigan. This reform has two components: property tax reduction and centralization of school funding at the state level, with increases for low-revenue districts and revenue caps for high-revenue districts.…”
Section: Many Researchers Have Examined State Level Public Education mentioning
confidence: 99%
See 2 more Smart Citations